Bajkopisna diseminacija mitoloških motiva u Pričama iz davnine Ivane Brlić-Mažuranić na primjeru intertekstualnih poveznica s leksikonom A. TkanyjaFairytalemanship-like Dissemination of Mythological Motives in Croatian Tales of Long Ago by Ivana Brlić-Mažuranić, Exemplified by Intertextual Connections with A. Tkany’s Lexicon - Engler, Tihomir; Kos-Lajtman, Andrijana (Studia mythologica Slavica, 2011)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">In this paper, the connections between Ivana Brlić-Mažuranić’s fairytales and Anton Tkany’s historiographic lexicon Mithologie der alten Teutschen und Slaven are being studied. Exemplified by the analysis of loaned motives, it is shown how intertextuality influences the styling of the author’s discourse. By taking into consideration the broader literary-historical context, the quilting point of the author’s fairy tales is trying to be established by considering her procedure of narrating mythological motives. Thus the position of the texts by Brlić-Mažuranić is seen as the juxtaposition of old folk tales and of so-called artistic fairy tales, which makes it possible to define the author’s discourse type as fairytalemanship, whose focal point is the impulse of preserving national heritage and especially the moral dimension of human existance.